Processing and Application of Tarum Leaves into Indigo Powder for Yarn Dyeing in Amol Village, North Central Timor District - Risna Erni Yati Adu; Marselina Theresia Djue Tea; Gebhardus Djugian Gelyaman; Jefry Presson (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Processing and application of tarum leaves into indigo powder for woven threads dyeing has been carried out in the Weaver Women's Group of Amol Village, North Central Timor District. The less knowledge in producing indigo-colored woven fabrics and unavailable source of Indigo leaves during the dry season are the main reasons to conduct this program. This program was carried out in 4 main stages, namely socialization, demonstration of Indigo leaves processing into indigo powder, application in yarn dyeing and evaluation. This activity was able to increase the knowledge and skills of the Weaver group in processing Indigo leaves which are abundant in the rainy season into indigo powder which can be stored for use in the dry season. The resulted powder has been applied in the coloring of the woven yarn to produce an indigo blue color.